Migraine treatment with external concurrent occipital and trigeminal neurostimulation—A randomized controlled trial. Issue 8 (24th June 2022) - Tepper, Stewart J.; Grosberg, Brian; Daniel, Oved; Kuruvilla, Deena E.; Vainstein, Gabriel; Deutsch, Lisa; Sharon, Roni
Abstract: Objective: To evaluate the efficacy and safety of concurrent non‐invasive stimulation of occipital and trigeminal nerves in acute treatment of migraine with or without aura. Background: Non‐invasive neuromodulation devices stimulating a single peripheral nerve or anatomic distribution are routinely used by patients with migraine refractory to the first‐line drugs or those who opt out of pharmaceutical treatment. Concurrent occipital and trigeminal stimulation was described in an invasive setting, and its safety cost outweighed its efficacy gain. This study evaluated the efficacy and safety of an external concurrent occipital and trigeminal device in acute treatment of migraine. Design and Methods: This was a randomized, sham‐controlled, double‐blind, multi‐center trial. Patients 18 years of age or older who met the International Classification of Headache Disorders (2018) diagnostic criteria for migraine with or without aura, reported 1–6 migraine attacks per month, and other headaches no more than 6 days per month were enrolled. Of 131 intention‐to‐treat participants (67 and 64 in the active and sham groups, respectively), 109 (50 and 59 in the active and sham groups, respectively) treated at least one migraine episode. Reduction of migraine headache (pain relief) 2 h after treatment initiation was the primary efficacy endpoint. Pain relief at 1 h, and pain freedom and relief in most bothersome symptom at 2 h after treatment initiation were the secondary endpoints. Freedom from most bothersome symptom at 2 h and sustained pain freedom 24 h after treatment initiation were among the exploratory endpoints. Results: Sixty percent of participants (30/50) in the active arm reported pain relief at 2 h after initiation of the first eligible treatment (primary outcome) compared to 37% (22/59) in the control arm (difference, 23%; 95% confidence interval [CI], 2%–41%; p  = 0.018). Pain freedom at 2 h without rescue medication was reported by 46% (23/50) of participants in the active arm and by 12% (7/59) of participants in the sham arm ( p  < 0.001). Pain freedom 2 h after the treatment and, subsequently, at 24 h, was reported by 4.25 times more participants in the active arm (36%; 18/50) than in the sham arm (8%; 5/59). The 28% difference was statistically significant (95% CI, 1%–43%; p  < 0.001). A 4.25‐fold difference was also observed comparing the proportion of participants free from pain and most bothersome symptom 2 h after the stimulation (47% [17/36] and 11% [5/45] in the active and sham arms, respectively; 95% CI, 14%–54%; p  < 0.001). Adverse events were not serious or severe. All study‐related events resolved without treatment. Conclusion: External concurrent occipital and trigeminal neurostimulation is a well‐tolerated, safe, and effective migraine treatment that provided a fast and durable relief and freedom from migraine pain and associated symptoms in a randomized setting. The observed safety and performance suggest external concurrent occipital and trigeminal neurostimulation is a viable alternative to the currently available acute migraine treatments. Trial registration: clinicaltrials.gov identifier NCT03631550.